TECHNOLOGY FOR OBTAINING NPS-FERTILIZERS BASED ON AMMONIUM NITRATE MELT, KYZYLKUM PHOSPHORITE, AND PHOSPHOGYPSUM - Mamataliyev Abdurasul Abdumalikovich,; Bozorov Ikrom Iskandarovich,; Ruziyeva Ugiloy Mamatraimovna, (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
Abstract: This article investigates the technology for obtaining multicomponent NPS-fertilizers based on ammonium nitrate melt, Kyzylkum phosphorite, and industrial waste—phosphogypsum. The study examines the influence of mineral additives on the physicochemical properties of the ammonium nitrate melt, specifically focusing on granule strength and hygroscopicity. The research results demonstrate that the addition of phosphogypsum and phosphorite enhances the thermal stability of the final product and enriches it with essential nutrients such as nitrogen, phosphorus, and sulfur.